Feasibility and repeatability of optical coherence tomography measurements of pre-stent thrombus burden in patients with STEMI treated with primary PCI. (20th September 2014) - Kajander, Olli A.; Koistinen, Laura S.; Eskola, Markku; Huhtala, Heini; Bhindi, Ravinay; Niemelä, Kari; Jolly, Sanjit S.; Sheth, Tej; Sheth, T.; Jolly, S.; Kassam, S.; Vijayraghavan, R.; et al.
Abstract: Aims: Intracoronary thrombus is disrupted by stent deployment and confounded by the development of intrastent plaque prolapse. This study aims at investigating the feasibility and repeatability of thrombus quantification prior to stent implantation using optical coherence tomography (OCT) in ST-segment elevation myocardial infarction (STEMI) patients. Methods and results: Patients were enrolled in an OCT substudy of the TOTAL trial (a randomized trial of routine aspiration ThrOmbecTomy with PCI vs. PCI ALone in patients with STEMI undergoing primary PCI) of aspiration thrombectomy or percutaneous coronary intervention (PCI) alone in primary PCI (PPCI) of STEMI. Using OCT, thrombus burden (TB) and other measures of pre- and post-stent atherothrombus were analysed over the arterial segment defined by the final stent length. Feasibility was 86.2% (25/29 patients) for both pre- and post-stent OCT imaging. Altogether, 8111 OCT cross-sections were analysed. In Bland–Altman analyses of inter-observer variation ( n = 25), the mean pre-stent TB was 8.76% for Observer 1 and 8.97% for Observer 2 (limits of agreement −2.6 to 2.2%). In Bland–Altman analyses of intra-observer variation ( n = 15), the mean pre-stent TB was 8.06% for the first and 7.35% for the second round of analysis by Observer 1 (limits of agreement −1.72 to 3.15%). There was a good correlation between pre-stent TB and pre-stent quadrants with thrombus/mm ( r = 0.97), but only modest correlation between pre-stent TB and post-stent atherothrombotic burden (ATB; r = 0.54). Conclusions: Measurement of pre-stent TB by OCT during the PPCI of STEMI is feasible and highly repeatable. Pre-stent TB is only modestly correlated with post-stent ATB, which indicates that pre-stent measurements might be of additional value when assessing the TB in STEMI.